Nitrosative Stress in Retinal Pathologies: Review - Antolin Cantó; Teresa Olivar; Francisco Javier Romero; María Miranda (MDPI AG, 2019)
Nitric oxide (NO) is a gas molecule with diverse physiological and cellular functions. In the eye, NO is used to maintain normal visual function as it is involved in photoreceptor light transduction. In addition, NO acts as a rapid vascular endothelial relaxant, is involved in the control of retinal blood flow under basal conditions and mediates the vasodilator responses of different substances such as acetylcholine, bradykinin, histamine, substance P or insulin. However, the retina is rich in polyunsaturated lipid membranes and is sensitive to the action of reactive oxygen and nitrogen species. Products generated from NO (i.e., dinitrogen trioxide (N2O3) and peroxynitrite) have great oxidative damaging effects. Oxygen and nitrogen species can react with biomolecules (lipids, proteins and DNA), potentially leading to cell death, and this is particularly important in the retina. This review focuses on the role of NO in several ocular diseases, including diabetic retinopathy, retinitis pigmentosa, glaucoma or age-related macular degeneration (AMD).